ONLINE COLLECTION FUND PLATFORMS: PEOPLE’S VIEWS ON “ASNAF CARE” (Practitioner Research, 2023)
Asnaf Care was introduced by the Kedah State Zakat Board (Lembaga Zakat Negeri Kedah or LZNK) on March 29, 2020. Asnaf Care is a fundraising system that uses an online system connected to the Internet to raise charity funds or donations to help the community in Kedah affected by the Covid-19 pandemic. Through this fund, LZNK aims to help 700,000 families. Nevertheless, judging from the data gathered by the Asnaf Care system, the collections could be more encouraging. This development is quite worrying and needs to be seriously examined for the factors and reasons that lead to this situation, namely the passive contributions to the Asnaf Care fund among the people of Kedah. A study was conducted to identify the factors that could contribute to the awareness of online charity contributions, especially for the Asnaf Care fund. This study used a questionnaire form as an instrument. A total of 250 respondents for this study are targeted at those aged 18 years and above and from various walks of life. Descriptive statistics are used to explain the findings of this study. The results indicated that almost half of the total respondents had never heard of this program. Similarly, the existence of the Asnaf Care campaign is also unknown to the people of Kedah. The findings of the study can be used to suggest some recommendations to the Kedah State Zakat Board on methods to spread awareness of online contribution among the people of Kedah so that the collection of Asnaf Care can be increased and able to achieve the target set by LZNK.